Carpologia de Couroupita guianensis Aublet (Lecythidaceae) II - Anatomia - Schoenberg, Maria Miranda (Acta Biológica Paranaense, 1983)
Carpologia de Couroupita guianensis Aublet (Lecythidaceae) II - Anatomia